Serial case reports: Pregnancy with Lucio's phenomenon of leprosy in dr. Soetomo hospital, Surabaya - Nareswari I. Cininta; M.I.A Akbar; Rozi A. Aryananda; Khanisyah E. Gumilar; Manggala Pascawardhana; Budi Wicaksono; E. Ernawati; Agus Sulistyono; A. Aditiawarman; Hermanto T. Joewono; M.N. Abdullah; Erry G. Dachlan (PAGEPress Publications, 2019)
Leprosy is a complex disease which will affect in many aspects of the patient. In dr. Soetomo hospital, there were two cases of pregnancy with leprosy and Lucio's phenomenon from 2014 until 2018. Both had been receiving multidrug therapy (MDT) before pregnancy but stopped due to lack of compliance. First case was resulted with term. Second case was admitted with worse condition than the first case, fetal growth restriction and ended with preterm delivery probably because the severity of the case. Lucio's phenomenon incidence is increased in pregnancy due to immunodeficient condition. This serial case report shows that the initial diagnosis and optimum treatment of leprosy is very important especially in women of child-bearing age.